2019
DOI: 10.1074/jbc.ra118.005549
|View full text |Cite
|
Sign up to set email alerts
|

SMAD family member 3 (SMAD3) and SMAD4 repress HIF2α-dependent iron-regulatory genes

Abstract: Hypoxia-inducible factor 2␣ (HIF2␣) directly regulates a battery of genes essential for intestinal iron absorption. Interestingly, iron deficiency and overload disorders do not result in increased intestinal expression of glycolytic or angiogenic HIF2␣ target genes. Similarly, inflammatory and tumor foci can induce a distinct subset of HIF2␣ target genes in vivo. These observations indicate that different stimuli activate distinct subsets of HIF2␣ target genes via mechanisms that remain unclear. Here, we condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…Interestingly, HIF-2␣ transcriptional targets involved in inflammation were not active despite activation of iron-absorptive genes. This finding is in line with recent work showing that HIF-2␣ functions with cofactors and other transcriptional partners to regulate subsets of target genes when the protein is stabilized (28,29). Future work will need to define how specific HIF target genes are regulated during unique environmental ques as well as the relative contribution of HIF-2␣ oxygen and iron sensing in different cells and tissues.…”
Section: Anemia Leads To Tissue-specific Stress Responsessupporting
confidence: 81%
“…Interestingly, HIF-2␣ transcriptional targets involved in inflammation were not active despite activation of iron-absorptive genes. This finding is in line with recent work showing that HIF-2␣ functions with cofactors and other transcriptional partners to regulate subsets of target genes when the protein is stabilized (28,29). Future work will need to define how specific HIF target genes are regulated during unique environmental ques as well as the relative contribution of HIF-2␣ oxygen and iron sensing in different cells and tissues.…”
Section: Anemia Leads To Tissue-specific Stress Responsessupporting
confidence: 81%
“…In mechanistic terms, we discovered two important and unexpected ways that SMAD4 promotes FZD4 transcription in ovarian GCs. First, SMAD4 directly controls FZD4 transcription by acting as a transcription factor, the best-characterized manner in which SMAD4 regulates its target genes 12,39,54 . The SMAD4 protein affects the transcriptional activity of target genes, usually by interactions between its DNA-binding domain and SBE motifs within the promoter region of target genes 55 .…”
Section: Discussionmentioning
confidence: 99%
“…The SMAD4 protein affects the transcriptional activity of target genes, usually by interactions between its DNA-binding domain and SBE motifs within the promoter region of target genes 55 . Intriguingly, the regulatory effect of SMAD4 on target genes can act in one of two opposing ways: it can promote target gene transcription by acting as a transcriptional activator 6,12 , or inhibit the transcription of target genes by acting as a transcriptional repressor 54,56 . In this study, we showed that SMAD4 is a new transcriptional activator of FZD4, and that the two factors form a novel regulatory axis that mediates crosstalk between the TGF-β and Wnt signaling pathways in porcine GCs.…”
Section: Discussionmentioning
confidence: 99%
“…Under hypoxia, which occurs in tumors or during inflammation, hypoxia inducible factors (HIF) are known to control iron regulatory proteins. HIF-regulated proteins are not only the transferrin receptor (TfR) and the divalent metal transporter 1 (DMT1), which are responsible for iron import, but also ferroportin (FPN), which is the only established iron exporter [ [4] , [5] , [6] , [7] ]. Iron storage is equally important and may prevent cells from oxidative stress caused by an overload with redox active free iron.…”
Section: Introductionmentioning
confidence: 99%